An Analysis of Students Writing Skill in Recount Text at the Tenth Grade of SMAN 1 Panggarangan Lebak-Banten - Ratih Dewi Lestari; Ari Fajria Novari; Riandi Riandi (English Language Education Department, Universitas Majalengka, 2022)
The aims of this research is to analyze students’ writing skill in recount text based on content, organization, grammar, and mechanism in writing recount text at the class X MIPA 2 of SMAN 1 Panggarangan Lebak-Banten. Students' skills in writing recount text entered the excellent category. which, if explained in more detail, four students (40%) got a score of 80-100 (excellent), three students (30%) got a score of 60-69 (poor), two sudents (20%) got a score of 70-79 (good averange), and one student (10%) got a score of 25 – 59 (very poor). The results of the analysis of several aspect, namely content, organization, grammar, and mechanics, showed that students mistakes in writing recount texts were dominated by the grammar aspect where (60%) students were wrong in grammar placement, it was triggered by a lack of knowledge about the grammar used in recount text. Based on the results of interviews, most of them difficulties in writing recount text are caused by difficulties in finding ideas, difficulties in grammatical placement, difficulties in arranging the sentences in paragraphs because the ideas for writing are very limited, hard to compile words in sentences to be a paragraphs, and lack of vocabulary makes it difficult for students to write recount text.